Does the 4th estate deliver? Towards more direct measure of political media bias - Ralf Dewenter; Uwe Dulleck; Tobias Thomas (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
This contribution introduces a new direct measure of political media bias by analyzing articles and newscasts with respect to the tonality on political parties and politicians. On this basis we develop an index sorting the media in the political left to right spectrum. We apply the index to opinion-leading media in Germany, analysing 7,203,351 reports on political parties and politicians in 35 media outlets from 1988 to 2012. With this approach, in contrast to other indexes, we are able to achieve a more direct and reliable measure of media bias. In addition, we apply the index to study whether the media fulfil their role as the fourth estate, i.e. provide another level of control for government, or whether there is evidence of government capture.
Keywords: C43; D72; L82; 330; media bias; governmental capture; index